Evaluasi Pengalaman Pengguna Aplikasi Streaming Music Menggunakan Metode User Experience Questionnaire - Alfarisi, Gitasari Kurnia; Fathoni, M. Yoka (Jurnal Ilmiah Wahana Pendidikan, 2023)
Along with the times, the use of music technology such as music streaming application services is also increasing. There are many music streaming applications in PlayStore, but there are two applications that are most downloaded, namely the Spotify and Resso applications. This study aims to determine the comparison of user experience evaluation results on two appli[1]cations, namely spotify and resso. This study uses a measuring instrument in the form of a user experience questionnaire (UEQ) which consists of six measurement scales and 26 question items. This study used 200 respondents who met the research criteria. The results of this study are that the spotify application has a positive impression on five scales, namely attractiveness, clarity, efficiency, accuracy, and stimulation. Meanwhile, the resso application has a positive impression on five scales, namely attractiveness, clarity, efficiency, accuracy, and novelty. Furthermore, it was found that most had significant differences in mean scores.